2001
DOI: 10.4269/ajtmh.2001.65.329
|View full text |Cite
|
Sign up to set email alerts
|

Spotted fever in Brazil: a seroepidemiological study and description of clinical cases in an endemic area in the state of São Paulo.

Abstract: Abstract. During 1985During -1995 clinically and epidemiologically compatible with Brazilian spotted fever were identified in 17 patients in the county of Pedreira, in the state of São Paulo, Brazil. Spotted-fever group rickettsial infection was confirmed by serology and/or immunostaining of tissues in 10 of these patients. Immunostaining confirmed infection in a 37-year-old pregnant patient, although rickettsial antigens were not demonstrable in the tissues of the fetus. A serosurvey was conducted in four lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
70
0
19

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(94 citation statements)
references
References 20 publications
4
70
0
19
Order By: Relevance
“…41 confirmed BSF cases of have been reported since 1985 (CVE 2006). The clinical severity (including high lethality), serological analyses, and isolation of Rickettsia from clinical samples of these cases were compatible with R. rickettsii (Lemos et al 2001, Angerami et al 2006. The presence of R. bellii and R. parkeri (strain Cooperi) was reported infecting the capybara tick Amblyomma dubitatum ), whereas R. felis was reported infecting fleas Ctenocephalides felis felis .…”
Section: Methodsmentioning
confidence: 87%
“…41 confirmed BSF cases of have been reported since 1985 (CVE 2006). The clinical severity (including high lethality), serological analyses, and isolation of Rickettsia from clinical samples of these cases were compatible with R. rickettsii (Lemos et al 2001, Angerami et al 2006. The presence of R. bellii and R. parkeri (strain Cooperi) was reported infecting the capybara tick Amblyomma dubitatum ), whereas R. felis was reported infecting fleas Ctenocephalides felis felis .…”
Section: Methodsmentioning
confidence: 87%
“…As compared with other Brazilian seroprevalence studies the rate found here for R. rickettsii was low. Lemos et al (1994Lemos et al ( , 2001), Del Guercio et al (1997), and Galvão et al (2002) found respectively 7.14, 4.2, 5.3, and 10.1% seroprevalence rates in different serosurveys. Despite this low seroprevalence rate, spotted fever group rickettsioses have been increasing in the studied region with an incidence of over 0.5/100,000 inhabitants-year (Costa 2004) compatible with the ongoing epidemic expansion recently reported from some Brazilian southeast regions (Rozental et al 2002, Galvão et al 2003.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, these cases cannot be considered confirmed cases of R. rickettsii infection. However, the severe clini- cal signs, high fatality rate and epidemiological data suggest that most of these cases were caused by R. rickettsii (Lemos et al 2001, Angerami et al 2006a. In fact, a few of these infections were investigated more thoroughly using molecular methods and were confirmed to be caused by R. rickettsii (Nascimento et al 2005, Rozental et al 2006, Lamas et al 2008).…”
mentioning
confidence: 99%